The development of job competency for skilled technical worker towards green technology - Ismail, Affero; Kasman, Zeti; Sumarwati, Sri; Nur Yunus, Faizal Amin; Abd Samad, Noorazman (GEOMATE International Society, 2019)
Promoting green technology to protect the environment is a major challenge in the current world. Human activity that affects the environment must be designed with a proper manner to ensure that the effort to maintain good practices is achieved. Referring to the above matter, an individual that entering the industry must be equipped with adequate skill and knowledge related to green skills. However, the scenario shows those individuals that enter the labor market without a relevant qualification is common in Malaysia. In the labor market, these individuals are considered to be low-skilled workers because they had no training prior to employment. Therefore, specific training needs to be prepared for them to increase their skills. Therefore, this research is conducted to develop a job competency for these groups of workers pertinent to its aim towards sustainable development. This research provided an opportunity to examine an enterprise-based approach to skill formation for workers with basic academic qualifications. Curriculum Development Based on Ability Structure (CUDBAS) methodology is used for this research where a structured curriculum development of human resources learning needs will be designed according to the job profile of the typical individual and group work. It will provide a clearer perspective on knowledge, competence and skill levels of employee behavior in performing tasks. The biggest impact on this study is to produce high skill employees concerning customer satisfaction and increased organizational productivity towards high-income nations.